Holocene History of the Greenland Ice Sheet based on Radiocarbon-dated Moraines in West Greenland. - Brink, Norman W. Ten (Meddelelser om Grønland, 1975)
The Greenland ice sheet margin retreated at least 125 km in West Greenland during the Holocene, but frequent halts or readvances interrupted the general trend and formed extensive moraine systems. Local deglaciation was synchronous with marine invasion of the fjords, resulting in deposition of interrelated glacial and marine sediments. The marine deposits have been uplifted by postglacial isostatic rebound and now occur as emerged-marine sediments and strandlines up to 125 ± 5 m a. s. l. The age and altitude values of 21 radiocarbon-dated samples of mollusc shells collected from the emerged-marine sediments define two postglacial emergence curves, which have been used to date moraine systems by means of their relations to former relative sea levels. Major moraine systems were constructed by the inland ice about 8800 B.P.,8300 B.P., ?300 B.P., 6500 B.P. to perhaps 6000?) B.P., and presumably c. 4800-4000 B.P. and 2500-2000 B.P. An advance of the inland ice about 3 km beyond its present margin c. 700 lichenometric years B. P. was followed by oscillatory retreat and advance, culminated by an advance 330 ± 75 C-14 years B.P. Moraines adjacent to the present ice margin were formed by a series of small advances culminated by local maxima between A.D. 1880 and 1920. The episodes of moraine construction were probably caused by slight decreases in mean temperature over periods of several decades to a few centuries, resulting in decreased ablation and immediate growth of the ice sheet margin. Long-term dynamic responses of the entire ice sheet, requiring thousands of years, were not necessary to form the moraines. The suggested short-term climatic cause of Holocene moraine construction is supported by palynologic and regional glacial geological evidence as well as historic temperature-glacier relations in West Greenland. Net retreat of the ice sheet margin during the Holocene was almost undoubtedly caused by hemispherewide climatic warming recorded in the 018/016 data for the Camp Century, Greenland, ice core as well as palynologic data from several sites in the Northern Hemisphere.